PERAN KEBANGSAAN MUHAMMADIYAH DI INDONESIA - Siregar, Fadillah Rosa; Sari, Yulan; Siregar, Rosmaimunah; Lubis, Jumaita Nopriani; Wahyuni, Sri (Tarim : Jurnal Islamic Eduation, 2023)
This study discusses the role of Muhammadiyah nationality in Indonesia. The purpose of his research is to find out what are the roles of Muhammadiyah for Indonesia. This type of research is library research. This research makes Library materials as its main data source. The results of the research obtained are, Muhammadiyah was founded by K.H Ahmad Dahlan in 1912 precisely in Yogyakarta. The purpose of Muhammadiyah is to uphold and uphold the religion of Islam so that a true Islamic society is realized. Muhammadiyah's efforts and activities are very broad, one of which is in the political field. Muhammadiyah has a very strategic role in the midst of the people and nation in the Unitary State of the Republic of Indonesia (NKRI). Muhammadiyah has a collective obligation to preach Islam in the form of beramar ma'ruf nahi munkar and provide ethical, moral and moral guidance to government and community policies. Muhammadiyah as a national force has fought in the independence movement and through its figures was actively involved in establishing the Republic of Indonesia. After Indonesia's independence, Muhammadiyah's devotion to the nation and state continued.